Immoral criminals? An experimental study of social preferences among prisoners - Birkeland, Sigbjørn
This paper studies the pro-social preferences of criminals by comparing the behavior of a group of prisoners in a lab experiment with the behavior of a benchmark group recruited from the general population. We find a striking similarity in the importance the two groups attach to pro-social preferences in both in strategic and non-strategic situations. This result also holds when the two groups interact. Data from a large internet experiment,matched with official criminal records, suggest that our main finding from the lab experiment is not influenced by the additional scrutiny experienced by participants in prison.Pro-social preferences; Criminals; Lab experiment